Synthesis of concentric ring antenna array for a wide isoflux pattern. (10th September 2014) - Reyna Maldonado, Alberto; Panduro, Marco A.
Abstract This research presents the synthesis of the concentric ring antenna arrays for a wide coverage pattern. The synthesis process is formulated as an optimization of the antenna excitations. Harmony search algorithm and particle swarm optimization are implemented for this optimization problem. The antenna array considers disk patches at the L‐band. First, the synthesis regards the behavior of the antenna array modeled by the cavity model. Second, the mutual coupling is included by using the full wave simulation. This synthesis could be very useful in satellites with terrestrial global coverage. The obtained antenna array provides a wide uniform power density and reduces considerably the hardware complexity for a satellite antenna system. Copyright © 2014 John Wiley & Sons, Ltd.